Determinants of Capital Structure in Retail Companies Listed on The Indonesian Stock Exchange - Sobir, Obing Zaid; Syah, Silvana; Buchdadi, Agung Dharmawan; Harisman (Journal of Business and Behavioural Entrepreneurship, 2023)
The determinant of the capital structure of retail companies listed on the Indonesia Stock Exchange (IDX) is the factors that influence how companies in this sector decide to finance their operations, including how they incorporate debt and equity into their capital structure. The capital structure is the comparison between debt and equity used by companies to finance their activities. This research aims to construct a concept and model and analyze the determinants of capital structure in retail companies in Indonesia using a Panel Data Regression approach. The research population includes all retail sector companies in Indonesia listed on the Indonesia Stock Exchange from 2017 to 2022. The capital structure is proxied by Debt Equity Ratio (DER). Meanwhile, the determinants of capital structure in this study consist of Profitability, Size, Growth, Liquidity, and Distance From Bankruptcy (DFB). The research shows that Profitability, Size, Growth, Liquidity, and Distance From Bankruptcy (DFB) significantly influence the capital structure policy. The results of this research can assist companies in making more informed financial decisions and can serve as a foundation for the development of policies that support the growth of the retail sector in the Indonesian capital market.